2020
DOI: 10.1038/s41586-020-2110-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA clamp function of the monoubiquitinated Fanconi anaemia ID complex

Abstract: The FANCI-FANCD2 (ID) complex, mutated in the Fanconi Anemia (FA) cancer predisposition syndrome, is required for the repair of interstrand crosslinks (ICL) and related lesions 1 . The FA pathway is activated when a replication fork stalls at an ICL 2 , triggering the mono-ubiquitination of the ID complex. ID mono-ubiquitination is essential for ICL repair by excision, translesion synthesis and homologous recombination, but its function was hitherto unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(133 citation statements)
references
References 33 publications
5
128
0
Order By: Relevance
“…Thus, FANCD2 could be recruited to chromatin by either unmodified PCNA, through its PCNAinteracting peptide (PIP) box (117), and/or by ubiquitinated PCNA through its coupling of ubiquitin conjugation to endoplasmic reticulum degradation (CUE) domain (118). Recent studies have demonstrated that unmodified FANCD2 does not bind to DNA (88,89). FANCD2 exists as a homodimer but in response to replication stress, FANCI is exchanged for one subunit of FANCD2, forming a FANCD2-FANCI (D2-I) heterodimer…”
Section: Midas Activation By Fancd2 Is Dependent On Pcna Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, FANCD2 could be recruited to chromatin by either unmodified PCNA, through its PCNAinteracting peptide (PIP) box (117), and/or by ubiquitinated PCNA through its coupling of ubiquitin conjugation to endoplasmic reticulum degradation (CUE) domain (118). Recent studies have demonstrated that unmodified FANCD2 does not bind to DNA (88,89). FANCD2 exists as a homodimer but in response to replication stress, FANCI is exchanged for one subunit of FANCD2, forming a FANCD2-FANCI (D2-I) heterodimer…”
Section: Midas Activation By Fancd2 Is Dependent On Pcna Ubiquitinationmentioning
confidence: 99%
“…that adopts an open conformation capable of binding DNA. Binding of DNA converts the D2-I complex into a closed conformation, and ubiquitination of FANCD2 by the FA core complex locks the complex on the DNA (88,89). Moreover, it is known that monoubiquitination of FANCD2 is carried out by the E3 ligase FANCL (119,120).…”
Section: Midas Activation By Fancd2 Is Dependent On Pcna Ubiquitinationmentioning
confidence: 99%
“…The molecular details of FANCI–FANCD2:DNA interactions were resolved in the cryo-electron microscopy (EM) structure of FANCI–FANCD2 bound to interstrand cross-linked double-stranded DNA (dsDNA) (PDB: 6VAA , average resolution 3.8 Å) ( Figure 1 C) [ 25 ]. The structure of FANCI–FANCD2 revealed that dsDNA runs though the heterodimer [ 25 ], consistent with biochemical studies that indicate dsDNA is required for monoubiquitination to occur [ 17 , 31 ]. Interestingly, the monoubiquitination sites remain buried in the complex, which retains the same open trough-like shape as apo FANCI–FANCD2.…”
Section: Introductionmentioning
confidence: 99%
“…The previously observed preferential binding of FANCI to DNA [ 28 , 32 ] suggests that the tight binding of FANCI to DNA acts as an ‘entry point’ for FANCI–FANCD2 binding to stalled replication forks. Both FANCI and FANCD2 C-terminal domains (CTDs) are required for DNA binding within the ID2 complex [ 21 , 25 ]. This finding is consistent with previous low-resolution cryo-EM structure of FANCI–FANCD2 showing a C-terminal ‘Tower’ DNA-binding domain in FANCD2 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation